IS HIGHER EDUCATION PEDAGOGY ENABLING UNDERGRADUATE STUDENT ENGAGEMENT, MOTIVATION AND AUTONOMY? - Jane Bartholomew (PUPIL: International Journal of Teaching, Education and Learning, 2026)
Set within a Higher Education context, this doctoral enquiry asks: ‘How well do institutions and educators understand the levels of motivation, engagement and autonomy of the contemporary learner?’ It examines the undergraduate students’ experience of the UK’s Higher Education (HE) system as it relates to the development of their engagement, motivation and autonomy. It adopts a pragmatist approach that aligns with interpretivist and generic qualitative methodologies, supported by grounded theory principles. It symbiotically explores the research participants’ perspectives and lived experiences within UK HE. The ‘Student Engagement’ phenomenon, together with the UK sector’s existing accountability-driven, neoliberal framework, provides the background context for the two-part Case Study employing a multimethod approach. Part One uses content analysis and grounded theory to examine the data from final year students’ written stories about their motivational learning experiences. Part Two uses semi-structured interviews with final-year students, lecturers and managers at three different UK universities, in sharing perceptions and experiences relating to ‘student engagement’, ‘motivation’ and ‘autonomy’. Research findings highlight students develop increased confidence and motivation when deeper, more personal connections are formed during their HE experiences, when collaborating with peers and in response to pedagogies promoting active learning. Findings also uncovered a lack of consensus of opinion relating to the purpose or meaning of the phrase ‘Student Engagement’, resulting in recommendations proposing the replacement of this multi-meaning phrase with that of ‘Student Autonomy’. Research outcomes include the development of tools as interventions to enhance the students’ self-awareness, independence and autonomy. First is the ‘Pedagogy Action Card’ (PAC) game designed for lecturers. This encourages peer and self-reflection relating to the impact of pedagogic practice on students. Second is ‘Bartholomew’s Taxonomy of Self: The motivated undergraduate student’. This tool invites all stakeholders to re-examine the student experience by considering personal growth and psychological development of undergraduate students’ during their course.